2015
DOI: 10.1177/0276236615574487
|View full text |Cite
|
Sign up to set email alerts
|

Imagery Induction Processes Differentially Impact Imagination Inflation

Abstract: Imagining a fictitious childhood event can lead to a false belief in that event’s occurrence, an effect called imagination inflation. However, the nature of imagery induction can vary considerably and such differences have not been systematically addressed in the literature. In the current study, participants provided confidence ratings for a series of events before and after imagery exercises. We manipulated imagery instructions (guided vs. prompted, a between-subjects factor) as well as event valence (positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
(118 reference statements)
0
13
0
Order By: Relevance
“…We included event valence as a factor because some studies have shown event valence affects imagination inflation (e.g., Bays et al., 2015). In a three-way analysis of variance (ANOVA) that included event valence, it did not have a significant main effect on confidence rating changes, and it did not interact with any other variables.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We included event valence as a factor because some studies have shown event valence affects imagination inflation (e.g., Bays et al., 2015). In a three-way analysis of variance (ANOVA) that included event valence, it did not have a significant main effect on confidence rating changes, and it did not interact with any other variables.…”
Section: Resultsmentioning
confidence: 99%
“…However, we used different critical events in Experiments 1 and 2 and found similar effects of imagination inflation suggesting that our findings are generalizable. Because some studies have reported that event valence affects imagination inflation (e.g., Bays et al., 2015; Sharman & Barnier, 2008), we had participants imagine a combination of positive and negative events (and neutral events in Experiment 2). Event valence did not affect imagination inflation and it did not interact with the other two variables in Experiment 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been found that imagination effects are typically greater in participants with higher visual imagery abilities (Horselenberg, Merckelbach, Muris, Rassin, Sijsenaar & Spaan, 2000;Johnson, Raye, Wang & Taylor 1979). In addition, imagery instructions that guide or prompt the use of sensory information, enhance imagination inflation effects (Bays, Zabrucky, & Foley, 2015), and can lead to detailed (but false) recollection and reduced source discriminability (Thomas, Bulevich, & Loftus, 2003). Finally, the visual perspective from which one imagines an event can also influence the magnitude of the inflation effect (Linder & Echterhoff, 2015;Marsh, et al, 2014).…”
Section: Explaining False Autobiographical Memorymentioning
confidence: 99%